Dynamics of Water and Other Molecular Liquids Confined Within Voids and on Surface of Lignin Aggregates in Aging Bio Crude Oils - Bonini, Massimo; Fratini, Emiliano; Faraone, Antonio (Frontiers in Chemistry, 2021)
Neutron scattering methods were employed to study the microscopic structure and dynamics of Bio Crude Oils (BCOs) and their lignin fractions. The structure of the carbonaceous aggregates was investigated using Small Angle Neutron Scattering to reveal a fractal hierarchy as well as a growth of the aggregates as the aging of the BCO proceeds. Elastic Neutron Scattering measurements indicate that BCO liquid phase, comprised of water and other hydrogenated molecular liquids, is in a state of extreme confinement. Quasi-Elastic Neutron Scattering yields information on the molecular motions, indicating that long range translational diffusion is suppressed and only localized dynamics take place on the tens of picosecond time range. The obtained results provide quantitative information on the molecular activity, as aging proceed, in these reactive materials of relevance as potential renewable energy sources.